2018
DOI: 10.1152/ajpheart.00337.2018
|View full text |Cite
|
Sign up to set email alerts
|

Progression of myocardial ischemia leads to unique changes in immediate-early gene expression in the spinal cord dorsal horn

Abstract: The pathological consequences of ischemic heart disease involve signaling through the autonomic nervous system (ANS). While early activation may serve to maintain hemodynamic stability, persistent aberrant sympatho-excitation contributes to the development of lethal arrhythmias and heart failure. We hypothesize that as myocardium reacts and remodels to ischemic injury over time, there is an analogous sequence of gene expression changes in the thoracic spinal cord dorsal horn, the processing center for incoming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…We further identified the differential binding genes through integrating analysis ChIP-seq and RNA-seq data. For the differential genes associated LMNA alone with euchromatin, we obtained 5 candidate genes (EGR2, NMB, CREBBP, PRF1, and TENM4), of which EGR2 and NMB have been reported to involve in myocardial ischemia and heart failure, respectively [ 30 , 31 ]. Although there are currently no reports about PRF1 and TENM4 involved in heart disease, we noticed that they may be related to LMNA mutation-associated DCM in our research; therefore, they may be the potential biomarkers of DCM, which needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified the differential binding genes through integrating analysis ChIP-seq and RNA-seq data. For the differential genes associated LMNA alone with euchromatin, we obtained 5 candidate genes (EGR2, NMB, CREBBP, PRF1, and TENM4), of which EGR2 and NMB have been reported to involve in myocardial ischemia and heart failure, respectively [ 30 , 31 ]. Although there are currently no reports about PRF1 and TENM4 involved in heart disease, we noticed that they may be related to LMNA mutation-associated DCM in our research; therefore, they may be the potential biomarkers of DCM, which needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…MIRI causes nociceptive chemical and electrical signals that affect dorsal root ganglia and the upper thoracic spinal cord ( 42 ). Previous studies have reported that spinal gene expression is associated with in the development of MIRI ( 9 , 27 ) and have identified the molecular mechanisms during MIRI ( 26 , 27 , 42 ); however, the impact of the spinal process during MIRI requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the spinal cord is closely associated with the occurrence and development of MIRI ( 9-11 ). Following cardiac ischemia and reperfusion, chemical mediators such as dynorphin and suppresses substance P within the myocardium activate cardiac afferent fibres projecting from the dorsal root ganglion to the upper thoracic dorsal horn of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Hic1, a transcriptional repressor that modulates the expression of cell-cycle genes, can affect heart function and be regulated by the IL-6/STAT3 pathway (Wen et al, 2019;Sulston et al, 2017). Gas1, pttg1, Nrtn, and Tnfrsf25 have also been identified as key molecules in the heart tissue by regulating tissue formation, metabolism, apoptosis of cardiomyocytes, and the interaction of cytokine-cytokine receptor in the JAK/STAT pathway Jiang et al, 2019;Saddic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%